EXPERIMENTAL AND THEORETICAL ANALYSIS OF N,N’-(ETHANE-1,2-DIYLBIS(4,1-PHENYLENE)) BIS(1-(THIOPHEN-2-YL)METHANIMINE) AND N,N’-(ETHANE-1,2-DIYLBIS(4,1-PHENYLENE))BIS(1-(4- METHYLTHIOPHEN-2-YL)METHANIMINE) SCHIFF BASE LIGANDS - Ulucam, Guhergul; Yenturk, Busra (Journal of the Chilean Chemical Society, 2019)
N,N’-(ethane-1,2-diylbis(4,1-phenylene))bis(1-(thiophen-2-yl)methanimine) and N,N’-(ethane-1,2-diylbis(4,1-phenylene))bis(1-(4-methylthiophen-2-yl) methanimine) ligands are formed by diamine and two aromatic aldehyde using Schiff base condensation method. Ligands are characterised by fourier transform infrared spectroscopy (FT-IR), 1H- and 13C- nuclear magnetic resonance spectroscopy (1H- and 13C- NMR) and mass spectroscopy (LC ESI/MS) methods. Furthermore, geometric properties such as bond lenghts, bond angles, dihedral angles, electronic properties, highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) energies are calculated by using Gaussian 09w program. Experimental and theoretical spectrum datas are compared.